2009
DOI: 10.3844/jcssp.2009.392.397
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Software Product Quality during the Software Development Life-Cycle: An International Organization for Standardization Standards Perspective

Abstract: Problem statement: The International Organization for Standardization (ISO) published a set of international standards related to the software engineering, such as ISO 12207 and ISO 9126. However, there is a set of cross-references between these two standards. Approach: The ISO 9126 on software product quality and ISO 12207 on software life cycle processes had been analysed to investigate the relationships between them and to make a mapping from the ISO 9126 quality characteristics to the ISO 12207 activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Software quality is in general hard to quantify [28,29], but there exist standardized software quality factors [30,31]. In this section we investigate our framework with respect to usability, reliability, portability, maintainability, expandability, efficiency, and scalability.…”
Section: Software Qualitymentioning
confidence: 99%
“…Software quality is in general hard to quantify [28,29], but there exist standardized software quality factors [30,31]. In this section we investigate our framework with respect to usability, reliability, portability, maintainability, expandability, efficiency, and scalability.…”
Section: Software Qualitymentioning
confidence: 99%
“…According to [1] as per ISO 9126 standard, quality is defined as ''the totality of features and characteristics of a product or service that bears on its ability to satisfy given needs. Al-Qutaish [3] observed that the ISO 9126 model for software quality and ISO 12207 on software life cycle processes may be analyzed to map the relationships between them for better measurement of software product quality [6] customized the ISO 9126 model to desirable software quality attributes for web applications which are reliability, usability, security, availability, scalability, maintainability, and time to market, Boegh [7] observed that software quality has also been defined in terms of two types of product characteristics: (i) external quality (how the product works in its environment), like usability and reliability, and (ii) internal quality (how the product was developed). According to Andreou and Tziakouris [5] ISO 9126 model, having six major characteristics, namely, Functionality, Reliability, Usability, Efficiency, Maintainability and Portability, along with their associated sub-characteristics can be suitably modified to a quality frame work for developing and evaluating the software components.…”
Section: A Software Quality Attributesmentioning
confidence: 98%
“…Software performance is considered in many software quality models [5,40]. Synthesizing these quality models, as shown in Table 1, the main aspects of software performance are time behavior [17,31,37], capacity [37], resource utilization [17,31,37], speed/throughput 1 [31] and efficiency [10,17,20,49].…”
Section: Software Performancementioning
confidence: 99%